The effect of foreign investment announcements on stockholders' returns : evidence from Singapore - Lian, Whye Meng (2015)
This research examines the effect of foreign investment announcements on the stock prices of companies listed in the Stock Exchange of Singapore (SES) and the Stock Exchange of Singapore Dealing and Automated Quotation (SESDAQ) over the period between 1992 to 1993 . Over 30 companies were used as the sample for this study and the stock prices were tested for abnormal returns using the mean adjusted return model proposed by Brown and Warner (1980, 1985). The cumulative abnormal returns of the stock prices were also studied and tabulated and the time period used was broken down into various intervals to study the trading implications of such foreign investment announcements. From the results, it seems that significant abnormal returns concurs with the announcements. This suggests that shareholders do enjoy abnormal returns from such announcements. In our attempt to test the efficiency of the local market, we also observe that there are traces of semi-strong efficiency. Since this research topic is relatively new and there could be trading implications, attention is also given to that aspect. From the results, it appears that speculators can trade profitably with such announcements.